A Systematic Review on Cybersecurity Threats and Challenges in Hospitals - Vishnu Sunil; Sherry P. Mathew (Acta Medica International, 2024)
The inception of cybercrime can be traced back to the late 1970s, a period that coincided with the early development of the computer information technology (IT) sector. Due to its system vulnerabilities, healthcare has become particularly vulnerable to digital assaults. Hardware, software, networks, operating systems, medical devices, processes, and users make this sector vulnerable. This report identifies healthcare cybersecurity issues and solutions and opportunities for improvement in response to rising threats. This review's methodology was organised so that it complies to PRISMA criteria. A thorough search was undertaken in Web of Science, Scopus, Google Scholar, Saudi Digital Library, ACM Digital Library, PMC, and NCBI/PubMed. The search strategy included threats, ransomware, cybercrime, healthcare, and hospitals. The above overview of “cybersecurity” includes technological and organisational measures. Healthcare organisations cybersecurity defence concerns were the focus of the research questions. The search technique targeted relevant literature from bibliographic databases to answer these research concerns. A total of 352 potential entries were obtained from the search in the chosen databases. Of these, 13 were manually picked following preliminary assessment. The study examined these studies, which fit its focus on “cybersecurity, dangers, and challenges,” in detail. Data confidentiality, integrity, and availability are the foundation of information security. The study examined cyberthreats and their cascade effects. The growing usage of varied technologies for sensitive patient data transfer makes it difficult for healthcare organisations to stay up with the newest cybersecurity breaches and threats. A cohesive and integrated strategy involving training programmes, awareness campaigns, and cyberattack information sharing is advocated to protect healthcare organisations from cyberattacks. To protect our infrastructure and provide excellent patient care, all healthcare workers must recognise and accept their role in cybersecurity risk management.